The Responsibility of Science - Mieg, Harald A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open acccess book provides an overview of issues of scientific responsibility. The volume comprises three types of contributions: first, analyses of the responsibility of science; second, analyses of the structural conditions for science and its responsibility; and third, normative versions of scientific responsibility. The questions and problems dealt with include science as a profession, ambivalence of research and dual-use, innovation vs. precaution, notions of responsibility, the role of science within society and its relation to human rights, as well as scientific and public discourses. The book addresses scholars in the fields of Science Studies and Research Policy.
Preface -- Part 1. Analyses of the Responsibility of Science -- 1. Responsibility in Science: The Philosophical View (Hans Lenk) -- 2. Science as a Profession and its Responsibility (Harald A. Mieg) -- 3. Corporate Responsibility: A Principle of Responsive Adjustment (Peter A. French) -- Part 2. The Social Sciences View: Structural Conditions for Science Responsibility -- 4. Science Policy: From the Linear Model to Responsible Research and Innovation (Philip Macnaghten) -- 5. European Law: The Precautionary Principle and Science-based Innovation in Europe (Ellen Vos & Kristel de Smedt) -- 6. History of Science: Ambivalence(s) in the Research and use of Nuclear Energy (Horst Kant) -- Part 3. The Scientists' Voice on the Responsibility of Science -- 7. Between Parrhesia and Fake: Scientific Responsibility Today (Rainer E. Zimmermann) -- 8. On the Responsibility of Science for Guaranteeing Human Rights: In the Fight Against Human Degradation, Racism, and Anti-Semitism (Klaus Fuchs-Kittowski) -- 9. The Ambivalences of the Digital: Humans and Technologies Between new Options (dreams) and (un)noticeable Losses (Hartmut Graßl et al.)- Index.
Keywords: Science -- Moral and ethical aspects; Science -- Philosophy; Mass media -- Moral and ethical aspects; Science Ethics; Philosophy of Science; Media Ethics